Cutaneous Leiomyomatosis – Case Report and Literature Review - Mihai MEHEDINTU; Razvan DANCIU; Alexandra CHELARIU; Andrei S. COMAN; Cristian R. JECAN (Modern Medicine)
Cutaneous leiomyomas are uncommon benign smooth muscle tumors that comprise of three distinct types such as piloleiomyoma, angioleiomyoma, and genital leiomyoma. The discovery in 2001 of the association between cutaneous leiomyomas, uterine leiomyomas in women, and an aggressive form of renal cell cancer (RCC) underscores the importance of accurate dermatologic diagnosis of CL so that appropriate cancer screening and counseling of patients and at-risk relatives can be instituted. The present case report will discuss the pathogenesis, clinical manifestations, diagnosis, and management of a piloleiomyoma.